'Good Policy' Gone Bad: Institutionalised Ranking of Citizens and Identity Conflicts in Nigeria. (December 2015) - Eke, Surulola James
Contrary to mainstream thinking, the existence of diversity does not necessarily condemn a state to instability and chaos. In fact, difference is a good ingredient for progress because each group contributes its unique experiences and peculiar qualities to the cause of a nation. To produce crisis, diversity must be worked on or manipulated. With a view to gaining deeper understanding of the factors that impact on identity diversity to create conflict in Nigeria, a number of conflict theatres in the country were examined. Having explored each case, the article notes that the policies of the colonial state, that emphasised group differentiation, laid the foundation for identity conflicts. The post-colonial state is just as guilty. Its administrative arrangement for managing diversity, the federal character principle (FCP), has failed to exploit the country's diversity to produce development. Instead, it has deepened the isolation of certain groups, thus, inhibiting national integration. Added to the deliberate manipulation of diversity for personal interests by the political class, the incidence of identity conflicts in the country can be explained. Going forward, the author stresses the need to review the FCP and close all loopholes in its enabling laws that allow for easy misinterpretation and deliberate misapplication.